Maple Wood (Acer caesium) for Tooth Pick-industry - Karnik, M. G.; Misra, A. K. (Indian Forester, 1964)
Treatments to remove the bitterness of the Maple wood (Acer caesium) have been tried to make the wood suitable for Tooth-pick industry. Boiling with water has been found to be the best treatment.